(untitled) (مجلة الفاروق للعلوم, 2026)
Retrofitting university campuses can be an effective strategy toward the realization of sustainability goals with maximum ecological and educational value. This paper focuses on Okan University’s Tuzla Campus in Istanbul, which already has several sustainable features such as solar panels, electric vehicle charging stations, and green spaces. The paper proposes further enhancements through ecological retrofitting measures, including edible landscaping, rainwater harvesting, grey water recycling, natural ventilation, and waste management systems that will help in improving its environmental performance. These will serve to make the campus not only less environmentally intensive but also an interactive learning environment where sustainable practices are actively demonstrated and taught. This research adopts the case study approach to study on-campus features, using site observation, document analysis, and secondary data as they are their alignment with the principles of sustainability. The proposed retrofits will discuss major weaknesses arising from such an analysis in terms of the underutilization of green spaces, inefficient systems for natural ventilation, and the lacking of a proper system for water and waste management. For instance, edible landscaping with native fruiting trees and herbs will increase biodiversity while providing hands-on learning experiences in sustainable agriculture. Retrofit the skylights with operable elements to enable improved air circulation, reducing demands for mechanical ventilation. Besides, a composting system would support compost for waste management and enrich this edible landscape. This research underlines the fact that ecological retrofitting is not only a technical upgrade but also a transformative process in which sustainability is integrated into the ethos of educational institutions. Okan University can reduce resource inefficiencies and establish a culture of ecological awareness to become a model for sustainable campus design. Such retrofitting not only enhances environmental performance but also offers hands-on tools for sustainability education, ensuring long-term ecological benefits and preparedness by students to address global environmental challenges.